SÍNTESE DE AMINAS E ALQUINOS ORTO-NAFTOQUINOIDAIS: UMA ESTRATÉGIA PROMISSORA PARA O TRATAMENTO DO CÂNCER - DA SILVA, Natan; COUTO, Aliziane; SILVA, Carlos; BRAND, George; OLIVEIRA, Geane; VALENÇA, Wagner (ANAIS DO ENIC, 2025)
.